Analytical politics - Hinich, Melvin J. (Cambridge University Press, 1997)
Analytical Politics is an introduction to analytical theories of politics, explicitly designed for undergraduate classes and for the professional interested in an overview. Analytical Politics tries to explain why societies take the political decisions they do and focuses on evaluating these decisions. We cannot evaluate how well governments perform without some baseline for comparison: What should governments be doing? The main questions in Analytical Politics involve the existence and stability of the center. An understanding of these issues is essential for anyone who hopes to evaluate the performance or predict the actions of democratic government.